Co-morbidities of diabetes mellitus among admitted stroke patients in a tertiary hospital - Sarower Islam, M.; Tanjum, Tasmia; Sarker, Shishir Sikto; Khademul Islam, M.; Saha, Chinmoy; Dutta, Rajib; Das, Nimai; Dey, Suman (International Journal of Research in Medical Sciences, 2024)
Background: Diabetes mellitus significantly impacts stroke risk and outcomes by influencing co-morbid factors and stroke patterns, guiding interventions to reduce diabetes rates and improve stroke outcomes. The aim of this study was to describe the distribution of co-morbidities of diabetes among hospitalized stroke patients. Methods: To describe the pattern of co-morbidities of diabetes among hospitalized stroke patients was a descriptive study. It was done in the department of Medicine of Sir Salimullah Medical College and Mitford Hospital from January 2015-June 2015. A total of 110 patients were enrolled in the study. Result: Patients averaged 56.95 years old (SD±6.594), with the majority (50%) aged 51-60 years. Among the 110 patients, 72 were male, most of whom (97.2%) were smokers. Half of the males had controlled diabetes, while all females had uncontrolled diabetes. Ischemic stroke affected 75% of males and 97.4% of females. About 80% of males had hypertension, compared to 92% of females. Dyslipidaemia was known in 29% of males and 37% of females. Kidney disease prevalence was low in both groups. More than half of both males (55.6%) and females (55.3%) were obese. Peripheral neuropathy was noted in 47% of males and 65.8% of females. Non-alcoholic fatty liver disease affected 28% of males and 21% of females. Conclusion: It's crucial to implement targeted strategies for preventing and managing stroke in diabetic patients, emphasizing education and raising public awareness about diabetes and its complications.